A pilot validation of CFD model results against PIV observations of haemodynamics in intracranial aneurysms treated with flow-diverting stents. (13th February 2020) - Li, Yujie; Verrelli, David I.; Yang, William; Qian, Yi; Chong, Winston
Abstract: Flow-diverting (FD) stents are one of three common modes of treating intracranial aneurysms, yet knowledge of their effect on haemodynamics is incomplete. We used particle image velocimetry (PIV) to measure spatially-varying velocity of blood-analogue fluid within a patient-specific aneurysm model, and compared the observed flow behaviour to predictions from a computational fluid dynamics (CFD) model. In PIV experiments we characterised the flow on multiple cross-sections for three different arterial flowrates (150, 250, 400 mL/min) after deployment of a commercially-available FD stent. Our flow-diverting (FD) stent model for CFD simulation was constructed using a permeability adapted from the literature. Aneurysmal haemodynamics without the FD stent treatment provided good similarities between CFD and PIV results, and the results with a Silk stent treatment also provided acceptable concordances, thereby validating the use of CFD as a convenient and flexible tool for investigating intra-aneurysmal flow dynamics after FD stent treatment. Furthermore, for the first time, the porous-medium FD model stent was validated to be both efficient and effective to predict the flow-diversion effects of a FD stent treatment with a patient-specific intracranial aneurysm. Through the qualitative and quantitative comparison of CFD predictions against the experimental outcomes, this study gives confidence for future studies on aneurysmal haemodynamics and FD stent treatment effects to use CFD simulation.